Professional philosophy: Inside the delivery of sport psychology service at Team Denmark - Henriksen, K.; Diment, G.; Hansen, J. (Sport Science Review, 2011)
The field of applied psychology has developed rapidly in Europe in the past four decades. In Denmark, the sports psychology profession has been characterized by a diversity of approaches with little overarching consensus on the professional philosophy and interventions strategies among consultants in the field. In 2008, Team Denmark established a sport psychology team with the aim to enhance the quality and consistency of applied sport psychology services. The team began their work by creating a professional philosophy. This paper describes the rationale, content, and implications of this philosophy, including: (a) basic beliefs and values; (b) theories of intervention and behaviour change; (c) objectives of the sport psychology intervention, (d) the content and focus of the interventions, and (e) sport psychological services and methods. High quality service requires coherence across all five levels of the philosophy. Implications of introducing the professional philosophy include a more unified service delivery across Denmark and the fact that sport psychology services are demanded more than ever in Danish elite sport.